Skeletons in the ditch: funerary activity in ditched enclosures of Porto Torrão (Ferreira do Alentejo, Beja) - Rodrigues, Filipa (2014)
Porto Torrão is a prehistoric settlement site in the Alentejo lowlands. The site is crossed by the Ribeira do Vale do Ouro (stream), which flows into the Sado River a few kilometers away from the archaeological site. The site is known since the early 1980’s for its impressive dimensions and important archaeological occupation, from Late Neolithic to the Bell Beaker period (Arnaud, 1982, 1993); rescue excavations have been carried out since 2003. A double-ditch system was recognized on the right bank of the stream during the archaeological intervention (Valera and Filipe, 2004). In 2008, archaeological work at the site was extended due to the implementation of an irrigation system, in connection with and paid for by the management of the Alqueva reservoir (EDIA, SA). A topsoil strip disclosed a large number of find-rich features (Rebelo at al., 2009), which were then excavated in the framework of a collaborative effort that brought together a number of archaeological companies. Among others, the features include a double-ditch system identified on both sides of the stream, several pits located inside and outside the enclosed area, megalithic graves (tholoi) and hypogea (Santos et al., in print; Valera, in print). Thus, the total area of the archaeological site extended up to >500 ha. This paper will discuss a particular type of funerary context excavated as part of the project, consisting of human skeletal parts mixed with faunal remains, sherds and stones. This context was found at the base of the inner ditch, on the left side of the stream. The human bones formed disorganized heaps and bore evidence that suggested defleshing. Both children and adults are present, but sexing of the remains has not been possible (Otte, 2010).